The effectiveness of different formulations of glyphosate herbicides under simulated rainfall conditions in controlling various weeds - Fajriani, Syifa; Kurniadie, Denny; Umiyati, Uum (Kultivasi, 2024)
Herbicide effectiveness is affected by herbicide formulation, rainfall, and weed type. Differences in glyphosate salt formulations and 2,4 D amine mixtures may result in variations in the herbicide's ability to wash off the herbicide due to rain. The aim of this study was to assess the effectiveness of different glyphosate herbicide formulations under varying rainfall in controlling various weeds. The experiment took place in a controlled greenhouse environment, utilizing a split plot experimental design with four replications.  The main plot was assigned to six different rainfall timings: 0 hours after application (HAA), 1 HAA, 2 HAA, 3 HAA, 4 HAA, and no rainfall. The subplots involved different herbicide formulations, namely isopropylamine glyphosate (h1), potassium glyphosate (h2), sodium glyphosate (h3) and glyphosate herbicide, IPA herbicide glyphosate + 2,4 D Amine (h4) and without any herbicide application (h0). Various parameters were observed, including weed dry weight and percentage of mortality growth. The results showed that the effectiveness of each herbicide formulation was diffent among weed specie under simulated rainfall conditions. Ageratum conyzoides can be controlled using isopropylamine glyphosate and potassium glyphosate with rainfall at 1 HAA. Axonopus compressus can be controlled by isopropylamine glyphosate and sodium glyphosate with rainfall at 1 HAA, while Borreria alata and Cyperus rotundus were effectively controlled by isopropylamine glyphosate with rainfall at 1 HAA.